Diseño y construcción de un prototipo para beneficio de minerales con fluidos magnetorreológicos a nivel de laboratorio (2016)
This article describes the procedures through which an apparatus can be designed to benefit from minerals with Magneto-Reological Fluids (MRF). It synthetically presents a review of current research, at the level of equipment and processes with the goal of obtaining a conceptual design, and applying the Frenc model to the mechanical design methodology. Based on the referenced bibliographical sources, calculations and analyses were performed for machine elements, material selection, modeling and manufacturing processes. Finally the developed apparatus is presented with the results of the trial runs. The project is based on prior research on obtaining MRF from magnetite, and developing a process to benefit from minerals with MRF; framed within a macro project, directed at promoting technological adaptations which allow the exploration and development of alternative techniques and technologies, aimed at optimizing processes and guaranteeing sustainable use of regional and national mineral resources.